Green Supply Chain: Studi Keterkaitannya dengan Kinerja Lingkungan dan Kinerja Finansial - Ayu Rohdayatin; Pudjo Sugito; Krisnawuri Handayani (University of Merdeka Malang, 2018)
This study aims to analyze the linkage of green supply chain management, environmental performance and financial performance. The research population are all restaurants in Malang with propotional random sampling as sampling technique. Primary data analysis technique using Partial Least Square (PLS). The result shows :1) green supply chain effect on financial performance, 2) green supply chain effect on to environmental performance, 3) environmental performance has no effect to financial performance, and 4) environmental performance does not mediate the influence of green supply chain to financial performance. It means, green supply chain is very important to improve financial performance, but environmental performance has not become a mediator in improving financial performance at restaurant business in Malang. https://doi.org/10.26905/jmdk.v6i2.2513